Upaya Meningkatkan Hasil Belajar Siswa Kelas IV Mengenai Operasi Bilangan Bulat Dengan Permainan Maju Mundur Siap Balik (Mamunsiba) Pada Pelajaran Matematika Di SD Negeri 13 Muara Telang - Siti Maesaroh Bina Satya Pertiwi; Muhammad Arif (Kilau Publishing, 2023)
This research aims to obtain data about student learning outcomes using the Mamunsiba game for class IV students at SDN 13 Muara Telang regarding integer counting operations. This research includes classroom action research. The subjects in this research were 24 class IV students at SDN 13 Muara Telang. Data collection was carried out by observation and final learning test. Data analysis was carried out descriptively. The results of the research showed that there was an increase in student learning completeness from 9 students or 37.5% pre-cycle, increasing to 15 students (62.5 percent) in cycle I, and 21 students (87.5 percent) in cycle II. Thus it can be concluded that the Mamunsiba game at SDN 13 Muara Telang improves the learning outcomes of class IV students regarding whole number arithmetic operations.